Numerical modeling of tribological behavior of hip joints - Ong, Han Qin. (2012)
Hip joint discomfort is one of the major problems experienced by elderly in the modern day society. Thus, there is a need to explore the possibilities to ease off the pain for those who are affected. Modelling the hip joint using finite element analysis (FEA) should be done to analyze the tribological behaviour of the joint. One case study will be presented to exhibit the effects of loadings on the hip joint based on the assumptions made. Apart from that, the factors to minimize the contact stresses on the hip joint and the ways to maintain a more durable hip implant will be discussed. After completing the FEA and cross-referencing with the research articles, it was concluded that the patient affected should constantly pay careful attention to the activities he is conducting in order to provide a longer life span to the artificial hip implant. This can reduce, but not totally eliminate, the chance of a second surgery at the affected joint.